Dynamic hybrid‐access control in multi‐user and multi‐femtocell networks via Stackelberg game competition. Issue 7 (1st May 2016) - Liu, Chengyi; Xing, Song; Shen, Lianfeng
Abstract : In this study, the hybrid‐access problem in multi‐femtocell networks, where multiple femtocell registered users (FRUs) and unregistered users (FURUs) coexist, is solved based on the optimal resource allocation using Stackelberg game. The main idea of the authors' proposed scheme is to have the femtocell base station (FBS) allocating resources to FRUs freely to guarantee their quality of service (QoS), and then obtaining the compensation for offering the hybrid‐access through selling the remaining resources to FURUs with high motivation. Based on the Stackelberg game involving the non‐cooperative competition among the FBS and multiple FURUs, a dynamic hybrid‐access control scheme is proposed and analysed for single‐femtocell access. Then a dynamic multi‐round hybrid‐access scheme (DMRHAS) with post‐DMRHAS is further designed for multi‐femtocell hybrid‐access. Simulation results show that the proposed schemes have the FBS not only protect FRUs' QoS, but also dynamically determine the list of accessible FURUs according to the channel power gains of FURUs and the change of FRUs' QoS demands, through pricing the FURUs.